2007
DOI: 10.1093/sw/52.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Practices among Dominican and Puerto Rican Mothers

Abstract: This study presents descriptive qualitative data about Latino parenting practices in an urban context. Focus groups were conducted with Dominican and Puerto Rican mother-adolescent pairs in the Bronx borough of NewYork City. When parenting style typologies are integrated with the Latino cultural components familismo, respeto, personalismo, and simpatía, Latino parenting practices and their underlying styles are better understood. Content analysis of parents' focus groups revealed five essential Latino parentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 43 publications
11
150
0
Order By: Relevance
“…Attitudinal adolescent familism has been associated with the perception of parents serving as legitimate sources of guidance and authority ( Bush, Supple, & Lash, 2004), such as for making decisions about dating ( Guilamo-Ramos et al, 2007). This perception of parents' legitimate authority leads to improved family functioning as well as positive adolescent outcomes, including less distress and more prosocial behaviors (e.g., Kuperminc et al, 2009).…”
Section: Family Functioningmentioning
confidence: 99%
“…Attitudinal adolescent familism has been associated with the perception of parents serving as legitimate sources of guidance and authority ( Bush, Supple, & Lash, 2004), such as for making decisions about dating ( Guilamo-Ramos et al, 2007). This perception of parents' legitimate authority leads to improved family functioning as well as positive adolescent outcomes, including less distress and more prosocial behaviors (e.g., Kuperminc et al, 2009).…”
Section: Family Functioningmentioning
confidence: 99%
“…Specifically, youth are expected to obey and respect their elders. Indeed, research has established that respect for parental authority is paramount for Mexican American families (Calzada et al 2010;Guilamo-Ramos et al 2007;Livas-Dlott et al 2010;Zucker and Howes 2009). Diaz-Guerrero (1994) termed this defining core value as affiliative obedience.…”
Section: Affiliative Obediencementioning
confidence: 99%
“…In a series of cross-national studies, these investigators found that, relative to youth in the United States, youth in Mexico endorsed higher affiliative obedience (DiazGuerrero 1994;Holtzman et al1975). It is important to note the affiliative obedience has been termed respeto (respect) in other research (e.g., Calzada et al 2010;Guilamo-Ramos et al 2007).…”
Section: Affiliative Obediencementioning
confidence: 99%
“…For example, Cuban American college students reported that their mothers were more protective than college students of Colombian, Venezuelan, or European descent (Escovar & Escovar, 1985). One study theorized that among Dominican and Puerto Rican families, the tenets of Latino parenting create an environment of close monitoring and a warm, supportive relationship (Guilamo-Ramos, Dittus, Jaccard, Bouris, & Acosta, 2007). A study of parenting styles among African…”
Section: Demographic Factorsmentioning
confidence: 99%